Conceptual BIM modeling in immersive virtual reality - O. Kysil (теорія та практика дизайну, 2017)
The article describes the problem of clarity in the design of today's architectural typology complexes, the analysis of the studies of foreign and domestic scientists. The general definition of BIM systems (Building Information Model) through the analysis of its components and hierarchy was made. The review of the leading engineering graphics packages was performed. Possibilities of this structure in conceptual creative plane, the purpose, boundaries and research methodology were highlighted. A list of software used in the study was given. It was concluded that virtual reality is a tool of research and education. The article proves the prospects of using CIM model (Concept Information Model), which is described in the research stages as part of the reconstruction of historic BIM modeling. In this paper the fact of evolution of the architect's thinking is ascertained.